Effect of Training, Job Loyalty and Job Satisfaction on Employee Work Productivity at Muhammadiyah Hospital Gresik - Zahrotul Firdaus; Sukaris Sukaris (Indonesian Vocational Research Journal, 2022)
The low level of work productivity is due to the lack of training received by employees. In addition, employee dissatisfaction with co-workers can lead to negative employee behavior towards the company and a decrease in commitment which in turn will reduce work productivity. This study aims to determine the effect of training, job loyalty and job satisfaction on work productivity in Gresik Muhammadiyah Hospital. This study uses a quantitative approach. The population in this study were employees of Muhammadiyah Hospital Gresik. The sample used is as many as 128 employees. The types and sources of data used are primary data in the form of answers to questionnaires from respondents. Analysis of the data used is Multiple Linear Regression Analysis. The results of the study concluded that the variables of training, job loyalty and job satisfaction had a positive and significant effect on work productivity at Muhammadiyah Hospital Gresik. This research can be used as a reference, but can use different research methods and indicators and hospitals. Muhammadiyah Gresik is expected to pay more attention to the ability of employees, especially job satisfaction, so that in the future it can increase productivity again according to the predetermined target. This study still has limitations, namely the limited time when distributing questionnaires due to the COVID-19 pandemic and sometimes respondents' answers differ from the actual reality